English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I know you divide it by 4 but i forgot what is the answer when you get the remainders what are the answers. i tried to read the book but couldn't understand. thanks

2007-01-21 10:52:21 · 7 answers · asked by ccutestuff2001 2 in Science & Mathematics Mathematics

7 answers

so you already know about dividing by 4
since
i x i = -1
i x i x i x i = 1
i^4 = 1

25 / 4 = 6 remainder of 1 translates to
i^25 = (i^4)^6 * i^1
remainder........^
answer is i

2007-01-21 11:02:40 · answer #1 · answered by Taras 2 · 0 0

i^0=1
i^1=i
i^2=-1
i^3=-i
i^4=1
...

So you are basically taking the remainder when the exponent is divided by four. If it is zero, then the answer is 1. If it is 1, the answer is i. If it is two, the answer is -1. If it is 3, the answer is -i. It follows that i^25=i

2007-01-21 10:59:25 · answer #2 · answered by XelaleX 2 · 2 0

xpress -2 in polar form = 2

2016-11-26 00:49:39 · answer #3 · answered by Anonymous · 0 0

i=i
i^2=i*i=-1
i^3=i^2*i=-i
i^4=i^3*i=1
i^5=i^4*i=i
and so on. Your answer is i (the remainder is 1, so you got i^1=i)

2007-01-21 11:00:24 · answer #4 · answered by Anonymous · 0 0

i^1 is just i

i^2 is -1 since i is the square root of -1

i^3, which is i^2 times i, is -1i or -i

i^4, which is i^2 times i^2 , is (-1)(-1) or 1

Here it repeats: i^5 = i^4 times i^1 =1 times i = i

i^6 = i^4 times i^2 = 1 (-1) = -1
etc

So if your remainder is 1, you get i

If it is 2, you get -1

If it is 3, you get -i

If it is 0, you get 1

2007-01-21 11:02:48 · answer #5 · answered by hayharbr 7 · 0 0

The key is to use mod 4. Each time you multiply i by itself, you in effect rotate it thru 90 degrees on the unit circle. So i^2 = -1 because you've rotated it thru 2x90 degrees and you're at (-1,0) on the unit circle. i^3 = -i because you've rotated it 270 degrees and you're at (0,-i) on the unit circle. Then with i^4 yo'ure back at 1 or (1,0) on the unit circle.
There's lots of good info online about this, see for example
http://www.math.rutgers.edu/~erowland/modulararithmetic.html

2007-01-21 11:06:55 · answer #6 · answered by Joni DaNerd 6 · 0 0

i^2 = -1
(-1)^2 = 1
therefore i^4 = 1.

You have:
i^25 = (i^1)*(i^24)
= i*((i^4)^6)
= i*(1^6)
= i

2007-01-21 11:01:10 · answer #7 · answered by Tim N 5 · 0 0

fedest.com, questions and answers